Large Format Ceramic Panels Versus Recycled Aluminum Casting Panels: Improvement of the Thermal Behavior of the Museum of Fine Arts of Castellón - Echarri Iribarren, Víctor; Gómez Castelló, Ginés; Rizo Maestre, Carlos (International Journal of Engineering and Technology, 2018)
There is a growing awareness towards the use in architecture of construction materials produced in the area in which the buildings are to be implemented. The reduction of environmental impacts derived from the lower consumption of energy in transportation is significant. In addition, the materials used in the façades have special relevance in the value of the annual energy demand. This fact becomes more important in the case of emblematic buildings with social media impact, both for the quality of their design and for the functional contributions they can make. Sometimes, even for purely aesthetic reasons, the paradox of opting for constructive solutions with worse performance, worse aging, a higher cost of maintenance operations or a higher value of annual energy demand is established. In this research the Museum of Fine Arts of Castellón is analyzed, made with cast aluminum recycled panels as a finishing material on the façade. A comparison is made with the alternative scenario, ventilated ceramic façade, of having used large format ceramic panels, produced in the region, where the ceramic sector is a very important cluster. The reduction of the value of the annual energy demand by 12% is evaluated by the improvements established in the ventilated ceramic façade.
Keywords: large format ceramic; annual energy demand; recycled aluminum; energy efficiency; ventilated façade